Intrauterine growth restriction and placental angiogenesis - Harma Muge; Harma Mehmet; Kandemir Nilufer; Gun Banu; Barut Aykut; Barut Figen; Aktunc Erol; Ozdamar Sukru (BMC, 2010)
Abstract Background Vascular endothelial growth factor (VEGF), basic-fibroblast growth factor (b-FGF), and endothelial nitric oxide synthase (eNOS) are factors that take part in placental angiogenesis. They are highly expressed during embryonic and fetal development, especially in the first trimester. In this study, we aimed to investigate the role of placental angiogenesis in the development of intrauterine growth restriction (IUGR) by comparing the levels of expression of VEGF-A, b-FGF, and eNOS in normal-term pregnancy and IUGR placentas. Methods The expression of VEGF-A, b-FGF, and eNOS was studied using the avidin-biotin-peroxidase method in placental tissues diagnosed as normal (n = 55) and IUGR (n = 55). Results were evaluated in a semi-quantitative manner. Results The expression of all the markers was significantly higher (p < 0.001) in cytotrophoblasts, syncytiotrophoblasts, extravillous trophoblasts, vascular smooth muscle cells, chorionic villous stromal cells, and villous vascular endothelial cells of the IUGR placentas when compared with those collected from normal-term pregnancies. Conclusion Increased expression of VEGF-A, b-FGF, and eNOS may be the result of inadequate uteroplacental perfusion, supporting the proposal that abnormal angiogenesis plays a role in the pathophysiology of IUGR.